Occurrence of Tomato Yellow Leaf Curl Virus on Volunteer Tomato, Jimsonweed, and Tobacco in North West Bank: Distribution of Virus Natural Reservoirs in Summer Season - Hazem Sawalha (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Volunteer tomato (Lycopersicon esculentum), jimsonweed (Datura stramonium) and tobacco (Nicotiana tabacum) plants were found to be natural reservoirs for Tomato Yellow Leaf Curl Virus (TYLCV) in the northern West Bank regions using the Polymerase Chain Reaction (PCR). The virus can be maintained in these plants during the summer period in the studied regions. Volunteer tomato plants proved to be the most significant reservoirs for the virus because they are so abundant in all of the studied regions, and they demonstrated a high rate of infection, ranging from 52-95%. The maximum infection of volunteer tomato plants was recorded in the Jericho district and Al-Far'a region to be 95% and 93%, respectively. Under field conditions, TYLCV was found to infect tobacco in one of two ways; either as crops planted near the tomato fields or as volunteer plants scattered in tomato growing sites in the Jenin districts. The maximum infection rate of volunteer tobacco plants and tobacco crops was recorded in Qabatyya to be 11% and 6%, respectively. The research showed that tobacco seedlings in nurseries can be infected with TYLCV by 3.5% in the Jenin district. Jimsonweed was discovered to be a natural host of TYLCV, however with low proportion and only in the Jericho district (one out of every two samples collected).